Local residents’ awareness towards the issue of mangrove degradation in Kuala Selangor, Malaysia - Asmawi, M. Zainora; Abd Rahman , Mazni Adibah (Elsevier, 2016)
Mangroves in Malaysia reside coastlines and the largest areas of mangrove are in the Northern Sabah. They sheltered at the shores of the west coast. Over four decades since 1980, mangroves are recorded to be declining due to various causes.Aquaculture practices implemented in the first decade; in Peninsular Malaysia was the key reason of mangrove depleting during the years. Public participation and their awareness are considered as important components in conserving the mangrove areas.Thus, the research was conducted to discover local residents awareness towards the issue of mangrove degradation in Kuala Selangor. A questionnaire survey was employed to a total of 103 respondents in Kuala Selangor. The findings suggest that lack of local residents’ awareness due to several reasons. In this regards, this research is to study the local residents’ awareness on the importance of mangrove areas.